2018
DOI: 10.1371/journal.pone.0198533
|View full text |Cite
|
Sign up to set email alerts
|

Wider perioperative glycemic fluctuations increase risk of postoperative atrial fibrillation and ICU length of stay

Abstract: IntroductionPostoperative atrial fibrillation (POAF) is a common complication following cardiac surgery associated with increased morbidity and mortality. Although sustained hyperglycemia is a known risk factor of AF and poor ICU outcomes, emerging in-vitro studies reveal acute glycemic fluctuations to be an additional independent predictor of AF. The effect of acute glycemic fluctuations on the incidence of POAF in the clinical setting remains unclear. We aim to investigate the effect of the magnitude of acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 27 publications
3
26
0
1
Order By: Relevance
“…Two studies demonstrated that elevated 24‐hour postoperative GV increased the risk of major adverse events after CABG, but not following isolated cardiac valvular surgery . In addition, a recent single‐center study from Singapore found that increased GV was an independent risk factor for POAF and increased intensive care unit length of stay in elective CABG patients . These retrospective studies align well with the results from two animal models which demonstrate that hyperglycemia and glucose fluctuations induce atrial fibrillation and aggravate arrhythmias …”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…Two studies demonstrated that elevated 24‐hour postoperative GV increased the risk of major adverse events after CABG, but not following isolated cardiac valvular surgery . In addition, a recent single‐center study from Singapore found that increased GV was an independent risk factor for POAF and increased intensive care unit length of stay in elective CABG patients . These retrospective studies align well with the results from two animal models which demonstrate that hyperglycemia and glucose fluctuations induce atrial fibrillation and aggravate arrhythmias …”
Section: Introductionsupporting
confidence: 76%
“…The results of this present study are consistent with prior reports that postoperative hyperglycemia and increased GV increase the risk of POAF . Sim et al performed a single‐center study of 1743 elective CABG patients in Singapore and demonstrated that wider postoperative glycemic fluctuation in the first 48 hours was an independent risk factor for POAF and increased ICU length of stay. Similar to the present study, they also reported that increased age and increased intraoperative blood transfusions were significant factors associated with PAOF in their univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… A meta‐analysis of studies with a long follow‐up period did show an increase in the incidence of AF that was proportional to the HbA1c . However, a study of type 2 diabetic patients who had undergone cardiac surgery did not show an association between HbA1c and post‐operative AF, although peri‐operative glycaemic fluctuations appear to increase the risk of post‐operative AF . In the ACCORD study, aggressive diabetes management with a target HbA1c of less than 6% failed to reduce the incidence of NAF compared to a target of 7.0% to 7.9% .…”
Section: Incidence and Frequency Of Atrial Fibrillation In The Type 2mentioning
confidence: 97%
“…In addition, one‐fifth of patients with CAD are affected by AF . The prevalence of AF after CABGS in patients with CAD has been reported to be about 15% …”
Section: Introductionmentioning
confidence: 99%